TARI KAIN DALAM RANAH INDUSTRI HIBURAN: SEBUAH PROBLEMATIKA KEMASAN DAN PELESTARIAN - Susmiarti, Susmiarti (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
This article aims at explaining the problems in traditional Kain dance in Painan Timur district, Pesisir Selatan regency. Nowadays problems in Kain dance revolve around its preservation and packaging. The presentation of Kain dance is no longer relevant with the growth of preference of entertaining art of the society. The preservation does not suit the sustainability of the Kain dance in the future. Therefore, Kain dance is no longer functional but marginal. The research is qualitative, where data is collected through observation, interviews, and documentation. The data is then analysed using ethnography and phenomenology. The research found that the weakness of traditional Kain dance in its presentation comes from its artistic movement aspect, dramatization, dynamics of the show, and originality of the costume and make-up. Besides that, the pattern of preservation is found only in keeping the training form of a specific place of the heir of the dance. There is no visible effort to further preserve the Kain dance in actual and effective model of its sustainability.